PENGEMBANGAN METODE BERCERITA BUDAYA LOKAL MELALUI MEDIA GAMBAR UNTUK MENINGKATKAN LITERASI BACA ANAK USIA 5-6 TAHUN - Rahmawati Ahmad; Suardi; Muhammad Yusri Bachtiar; Herlina; Hajerah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is how to develop a storytelling method through picture media. This development research aims to (1) find out How the need for the development of storytelling methods in improving children's reading literacy understanding (2) Researchers aim to find out How the prototype of early childhood storytelling methods that can improve children's reading literacy (3) Researchers aim to find out How the validity and practicality of children's storytelling methods to improve children's reading literacy (4) How the effectiveness of the method of telling stories of cultural figures through picture media to improve children's reading literacy. This type of research is development research with Addie model research design. The data collection techniques used in this research are questionnaires, interviews, observation and documentation. The subjects in this study consisted of 3 teachers and 13 children of group B Balqis Kindergarten The data analysis techniques used were qualitative data analysis and quantitative data analysis. The results showed that (1) the description of the need for the development of local cultural storytelling methods through image media to improve reading literacy for children aged 5-6 years is needed by teachers because local cultural storytelling methods through image media have increased and are very effective, (2) the design of the development of local cultural storytelling methods through image media is designed with a sequence of instrument preparation, namely: needs analysis, teacher response questionnaire, early childhood literacy level assessment, and (3) the level of validity and practicality of the development of local cultural storytelling methods obtained the results of 3.73 with very valid criteria, and the practicality of the development of local cultural storytelling methods obtained the results of 93.75% with very valid criteria. While in effectiveness, the results obtained were 96.43% with the Highly Effective category. It can be concluded that the local culture learning method can improve early childhood literacy skills.